TEACHER QUESTIONS IN SMK TUNAS JAYA TANAH JAWA - Anta Ovia Bancin; Rika (Universitas Negeri Medan, 2018)
The study deals with teacher questions during teaching learning process in SMK Tunas Jaya Tanah Jawa. The objectives of the study were to find out the types of questions used classification of questions based on Richards and Lockhart, and to reveal the reasons of questions that English teacher asked in the classroom used Richards and Lockhart’s reasons why teacher asked questions. The design of the research was a descriptive-qualitative research. The data were the transcriptions of teaching learning process collected by recording the observation and interview. The result showed that teacher asked three types of questions; convergent questions, procedural questions and divergent questions. The reasons why teacher asked questions were (a) to check students’ understanding, (b) to encourage students to think and focus on the lesson, (c) to encourage students’ participation in a lesson, (d) to clarify what student has said, (e) to elicit particular structures and vocabulary items, and (f) to stimulate and maintain students’ interest. It could be concluded that teacher asked many questions during teaching learning process and it could be a good technique for classroom interactions but it would make students bored, if teacher didn’t prepare well all the questions. Teacher should be aware of asking question for the students to consider the question type, and the reasons why the question should be asked